ANTIDIPLOMACY IN RUSSIA’S POLICIES REGARDING RUSSIAN-SPEAKERS IN THE BALTIC STATES - Kuczyńska-Zonik, Aleksandra (Baltic Journal of Political Science, 2017)
Though Russia is a classic realist power, Russia, as its recent actions in Ukraine reveal, frequently prefers hard power to powers of attraction. In addition to traditional economic pressure and military policy, Russia also employs antidiplomatic tools to influence the Baltic states. Though Russia officially proclaims itself a democratic state, it has been developing a broad spectrum of antidiplomatic methods to legitimise Russia’s interests in post-Soviet spaces inhabited by large numbers of Russian-speakers. The clearest example of these methods appears in Russia’s use of international and regional organizations’ conferences to express and articulate its interests in protecting Russian diasporas—a phenomenon that first appeared in the Vladimir Putin’s foreign policy as part of his efforts to construct a negative image of the Baltic states, affect the Baltic states’ domestic policies, and subtly discredit their governments. Russia is positioning itself as the protector of a Russian diaspora wounded by the Baltic states’ anti-Russian policies.